SOLUBILITY ENHANCEMENT OF RITONAVIR BY HOT MELT EXTRUSION - Desai, Sanjeevani; Disouza, John; Musle, Kiran; Avinash, Hoshmani (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The enhancement of oral bioavailability of poorly water-soluble drugs remains one of the most challenging aspects of drug development. Therefore formulation approaches are being explored to enhance bioavailability of poorly water-soluble drugs. The aim of the present study was to prepare and characterize solid solution of water insoluble anti-HIV drug (Ritonavir). Methods: There are various techniques such as micronization, solubilization, salt formation, complexation with polymers, change in physical form, use of prodrug and drug derivatization, alteration in pH, the addition of surfactants, and others are used by which the dissolution and bioavailability of sparingly soluble drugs can be improved. Among the various approaches, the solid dispersion (SD) technique has often proved to be the most successful in improving the dissolution and bioavailability of the poorly soluble drug. Solid Solution were prepared by Hot Melt Extrusion technique at 1:1.5, 1:2 (Ritonavir: Soluplus) and 1:1.5:0.5 (Ritonavir: Soluplus: Leutrol F68/leutrol 127/TPGS) ratios respectively. Solid Solution was evaluated for Saturation solubility, dissolution rate, XRD, FTIR, DSC and SEM. Results: Among all prepared Solid solution systems, the systems which contain 1:2 ratios of Ritonavir and Soluplus, has shown 13 fold increases in solubility than pure Ritonavir. DSC, XRD and SEM results shown to change from crystalline to amorphous form for all ratios of Ritonavir. Conclusion: From the above results, it was concluded that the improved drug dissolution could be achieved by formulating Ritonavir as a solid solution with the polymers such as Soluplus. The low hygroscopicity and low glass transition temperature of Soluplus make it particularly suitable for hot melt extrusion. Keywords: Solid solutions, Hot melt extrusion, Bioavailability, Soluplus